Moderate Enlightenment Based on The Qur'an in Islamic Higher Education: Social-Cultural Education Strategies to Achieve Sustainable Development Goal (SDG) 16 : Enlightenment Based on The Qur'an in Islamic Higher Education: Social-Cultural Education Strategies to Achieve Sustainable Development Goal (SDG) 16 - Miftah Ulya; Ahmad Ari Masyhuri; Chairunnisa Chairunnisa; Fahmi A Jawwas; Subur Wijaya (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2025)
Religious moderation has become a strategic agenda in Islamic higher education, especially in Malay communities faced with the challenges of religious polarization and the strengthening of extremist narratives. This study aims to analyze moderate Islamic preaching based on the Qur'an as a socio-cultural strategy in supporting the creation of peace and social justice in line with Sustainable Development Goal (SDG) 16. This study uses a qualitative approach with a thematic interpretation (maudhu'i) method combined with socio-religious analysis. The primary data consists of verses from the Qur'an that emphasize the principle of moderation, such as the concept of ummatan wasaṭan (QS. al-Baqarah [2]: 143) and the method of wise preaching (QS. an-Naḥl [16]: 125). while secondary data comes from academic literature on da'wah, religious moderation, and Islamic higher education in the Malay context The results of the study show that moderate Qur'anic da'wah in Islamic universities operates through three main dimensions: epistemic moderation through balanced interpretation of the Qur'an, pedagogical moderation through inclusive campus da'wah practices, and socio-cultural moderation in harmony with Malay cultural wisdom. These three dimensions contribute to strengthening social harmony, preventing religious extremism, and forming peaceful academic communities, as emphasized in the principles of justice and peace (QS. an-Naḥl [16]: 90). The core of this research lies in the interpretation of Islamic da'wah not only as a religious activity, but as an institutional and cultural mechanism of Islamic higher education in supporting sustainable peacebuilding and strengthening SDG 16.